Down-regulation of GCLC is involved in microcystin-LR-induced malignant transformation of human liver cells. (1st June 2019) - Jia, Xuejiao; Guan, Bin; Liao, Juan; Hu, Xinmei; Fan, Yu; Li, Jiangheng; Zhao, Huiliu; Huang, Qiuyue; Ma, Zhixing; Zhu, Xuefeng; Fei, Mengxue; Lu, Guodong; et al.
Abstract: Microcystin-LR (MCLR) is a potent hepatotoxin which could lead to the development of hepatocellular carcinoma. However, the mechanisms of its carcinogenic action remain obscure. The catalytic subunit of glutamylcysteine ligase (GCLC) primarily regulates de novo synthesis of glutathione and is central to the antioxidant capacity of the cell, but emerging data suggest that the GCLC expression is associated with cancer development. The purpose of this study was to investigate the role and molecular mechanisms of GCLC in MCLR-induced malignant transformation of a human liver cell line WRL68. During MCLR-induced cell transformation, the expression of GCLC and activity of glutamate-cysteine ligase (GCL) decreased continuously, accompanied with consistent low levels of glutathione (GSH) but high levels of oxidative DNA damages. Furthermore, MCLR markedly inhibited protein phosphatase 2 A (PP2 A), and increased the level of GCLC phosphorylation. In contrast, overexpression of GCLC significantly enhanced the levels of GSH, inhibited oxidative DNA damages, and suppressed MCLR-induced cell invasion and migration, as well as tumor growth in nude mice. GCLC overexpression partially attenuated MCLR-induced PP2 A inhibition. Together, the current results suggest that down-regulation of GCLC is involved in MCLR-induced malignant transformation of human liver cells by inducing oxidative stress.